Pengaruh Literasi Keuangan, Gaya Hidup dan Sikap Keuangan Terhadap Perilaku Keuangan Mahasiswa Pengguna Shopee Paylater - Fifie Dea Angelista; Leriza Desitama Anggraini; Andini Utari Putri (Journal of Trends Economics and Accounting Research, 2024)
Financial Behavior is an individual's way of managing, spending and making decisions regarding the money they have. Financial behavior is influenced by various factors, including knowledge about finance, lifestyle and financial attitudes. This research aims to examine the influence of financial literacy, lifestyle and financial attitudes on the financial behavior of students using Shopee Paylater. This research is a quantitative descriptive type with the primary data source coming from distributing questionnaires. The population in this research are students from the Faculty of Economics at Indo Global Mandiri University Class of 2020-2023 who use Shopee Paylater. The number of samples in this research was 100 students using the Slovin formula. The sampling technique uses a non-probability method with purposive sampling technique. The analysis technique in this research uses multiple linear regression, coefficient of determination, t test and F test. The results of this research show that financial literacy ( ) has a positive and significant effect on financial behavior (Y). Lifestyle ( ) has a positive effect on financial behavior (Y). Financial attitude ( ) has a positive effect on financial behavior (Y). Financial literacy, lifestyle and financial attitudes simultaneously have a significant effect on financial behavior.